Some Semantic and Morphological Peculiarities of Sharakans of VII-VIII Centuries - SANTURJYAN, MARI (Bulletin of Yerevan University B: Philology, 2021)
In the VII-VIII centuries Armenian Holy Hymn Canon (Sharakan) History initializes a new stage: authors working during this period (Komitas Aghdzetsi, Sahak Dzoraporetsi, Hovhan Odznetsi, Stepanos Syunetsi, Sahakadukht) create Sharakans rich in scriptural, Christian and national Holy Hymn topics, Canon is included in chronicles. Through linguistic investigation of Sharakans, it is possible to make an idea about the linguistic patterns of this genre. This article investigates morphological realities of Sharakans, considering which we especially tried to find out if Sharakans have deviations from Grabar (old Armenian) or not. Investigating some noticeable linguistic characteristics of such parts of speech as nouns, adjectives, numerals, pronouns, verbs, etc., it is found out that there is little difference between the morphological system of Sharakans and classic Armenian. The differences have semantic and syntactic character.